2023
DOI: 10.1159/000530831
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Top 100 Most-Cited Papers Concerning Dental Fluorosis

Abstract: A high number of citations can indicate the potential of any specific paper to influence other research and generate changes in clinical practice. Analyzing the most-cited papers in a certain scientific field may assist researchers to identify the influential papers as well their main characteristics. The present study aimed to analyze the 100 most-cited papers concerning dental fluorosis (DF) through a bibliometric review. A search was performed in the Web of Science Core Collection database (WoS-CC) in Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In our bibliometric study, the total number of citations in WoS-CC was 24,030, with individual studies ranging from 120 to 1161 citations. These metrics are noteworthy and align with findings from previous bibliometric studies, demonstrating the significance of our research in comparison to other dental analyses (Goebel et al, 2023;Paschoal et al, 2022;Rocha et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our bibliometric study, the total number of citations in WoS-CC was 24,030, with individual studies ranging from 120 to 1161 citations. These metrics are noteworthy and align with findings from previous bibliometric studies, demonstrating the significance of our research in comparison to other dental analyses (Goebel et al, 2023;Paschoal et al, 2022;Rocha et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Bibliometric studies map existing concepts, usually through citations, revealing the trends of scientific research and the main methodological tools used (Ahmad & Slots, 2021;Fardi et al, 2017;Gogos et al, 2020;Rocha et al, 2022). Citation analysis is the most employed method in bibliometrics, in which highly cited studies indicate the research interests of certain period of time, the relevance and merit of articles, as well as the importance of scientific journals (Hutchins et al, 2016;Perazzo et al, 2019).…”
mentioning
confidence: 99%
“…The system presented proved to be more sensitive, detailed and had the distinction of describing histological characteristics related to the macroscopic alterations of fluorosis. A recent bibliometric study [22], specifically on dental fluorosis, also highlighted the relevance of that study.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the limited number of randomized clinical trials (RCTs), it was observed that the publication of this study design has been increasing in recent years in JERD. It is acknowledged that RCTs are widely regarded as the “gold standard” in the evaluation of treatments, serving as a crucial reference to guide healthcare professionals' decisions 25 …”
Section: Discussionmentioning
confidence: 99%